THE INFLUENCE OF DHIKR AND PRAYER ON MENTAL HEALTH IN ADOLESCENTS AT THE SUBUL EL SALAM ISLAMIC BOARDING SCHOOL, INDONESIA: A NON-EQUIVALENT CONTROL GROUP DESIGN - Sarah Haya Fitria; Lastri Mei Winarni; Nurry Ayuningtyas Kusumastuti (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2026)
Background: Many problems that teenagers face today, such as social interaction, academic pressure, and searching for identity, can lead to mental health issues like stress, anxiety, and depression. Religion can help teenagers feel calm, clear their minds, and manage their behavior well, one of which is through activities like dhikr and prayer. Purpose: To determine